2004
DOI: 10.1007/s00204-003-0540-1
|View full text |Cite
|
Sign up to set email alerts
|

Aroclor 1254 inhibits tryptophan hydroxylase activity in rat brain

Abstract: Previous studies have shown that oral exposure of rats to polychlorinated biphenyls (PCBs) results in reduced 5-hydroxytryptamine (5-HT) concentrations in certain brain regions. In the present study, we investigated whether the PCB mixture Aroclor 1254 (0.33 mg/g body weight as a single oral dose) can inhibit the activity of tryptophan hydroxylase (TPH), the rate-limiting enzyme in 5-HT synthesis, and reduce 5-HT concentrations in selected brain areas. In two separate experiments, Aroclor 1254 exposure consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…Our results are consistent with observations that environmental or pharmaceutical substances that disrupt monoaminergic neurotransmitter functions in the hypothalamus, including pesticides [56, 57] and PCBs [58, 59], affect GnRH and LH release. The popularity of MDMA among humans has increased in recent years [1], leading to concern over the potential health hazards associated with recreational drug use.…”
Section: Discussionsupporting
confidence: 81%
“…Our results are consistent with observations that environmental or pharmaceutical substances that disrupt monoaminergic neurotransmitter functions in the hypothalamus, including pesticides [56, 57] and PCBs [58, 59], affect GnRH and LH release. The popularity of MDMA among humans has increased in recent years [1], leading to concern over the potential health hazards associated with recreational drug use.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, the rate-limiting step in serotonin synthesis, tryptophan hydroxylation, was significantly inhibited through decreased enzymatic activity of TPH in the hypothalamus. As mentioned earlier, studies in the pubertal male rat showed similar effects of A1254 treatment on the biosynthesis of serotonin [53]. Individual PCBs also affect gonadotropin levels.…”
Section: Hypothalamic-pituitary-gonadal Functionmentioning
confidence: 51%
“…Among these neurotransmitters is serotonin, which modulates LH secretion through actions on hypothalamic GnRH neurons [52]. Activity of the ratelimiting enzyme in serotonin synthesis, tryptophan hydroxylase (TPH) was reduced in the hypothalamus of pubertal male rats acutely exposed to A1254 [53], suggesting that the stimulatory effect of serotonin on GnRH-induced LH secretion may be disrupted by PCB inhibition of TPH. Other neurotransmitter systems may be similarly affected by PCBs, which have been shown to alter dopaminergic neurotransmission, among others, in puberty and adulthood [54].…”
Section: Pcb Effects On Pubertymentioning
confidence: 99%
“…Evidence has accumulated that polychlorinated biphenyls (PCBs) impair the function of serotonergic and other monoaminergic neurotransmitter systems in vertebrate brains (Seegal, 1996;Khan and Thomas, 2004). PCBs reduce serotonin (5-hydroxytryptamine; 5-HT) concentrations and increase the metabolite (5-hydroxyindolacetic acid, 5-HIAA) to 5-HT ratio both in rats (Seegal, 1996;Chu et al, 1996) and in the Atlantic croaker, Micropogonias undulatus (Khan and Thomas, 1997).…”
mentioning
confidence: 97%